Identification of Potential Tropical Maize Inbred Lines with Early Maturity for Drought-Prone Environments - Sree, K. Kavya; Kumar, M. V. Nagesh; Ramya, V.; Sunil, N.; Bhadru, D.; Chary, K. Srinivasa (International Journal of Bio-resource and Stress Management, 2024)
The present study was undertaken during October, 2020–January, 2021 at Maize Research Centre, Professor Jayashankar Telangana State Agricultural University, Rajendranagar, Hyderabad, Telangana state, India to identify potential inbred lines and hybrids with early maturity and high yield through combining ability analysis and heterosis. Six lines and four testers were crossed in L×T design to obtain 24 crosses. Evaluation of these crosses and their parents for combining ability revealed significant differences due to lines, testers and their crosses indicating the existence of wider variability among the material used in the study. Maize line MGC 434 (91 days), two testers GP-170 and PFSR-56 (91 days), and one hybrid MGC-445×PFSR-132 (83 days) were identified as early duration genotypes. Four lines MGC-444 (-3.13), MGC-440 (-2.71), MGC-439 (-1.96) and MGC-445 (-0.46) with significant negative GCA effects were identified as best general combiners for early maturity. Eight hybrids, MGC-439×BML-14 (-4.99), MGC-445×PFSR-56 (-4.65), MGC-461×PFSR-56 (-3.65), MGC-445×PFSR-132 (-3.60), MGC-434×BML-14 (-2.32), MGC-439×GP-170 (-2.10), MGC-440×PFSR-56 (-2.07) and MGC-440×GP-170 (-1.01) with significant negative SCA effects were considered as best cross combinations with early maturity. The inbred parents and cross combinations with early maturity identified in the study can be utilized for development of hybrids suitable to drought prone environments.